2009
DOI: 10.1021/om9003835
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Organometallic Benzo[b]thiophene Derivatives with Potential Antitumor Properties

Abstract: The incorporation of organometallic moieties into the structure of known active drugs to improve their therapeutic properties has gained considerable interest in recent years. The benzo- [b]thiophene derivative raloxifene is a selective estrogen receptor modulator (SERM) that has been found to decrease breast cancer risk in postmenopausal women compared to placebo. The current data suggest that, in the postmenopausal setting, raloxifene may have the benefits of the widely used tamoxifen with fewer side effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Another class demonstrates the enthusiasm researchers have for grafting metallocenes and metal carbonyls to a variety of biomolecules to modify their biological effects. [12] These therapeutic bioconjugates include steroidal [13][14][15] and nonsteroidal [16][17][18][19][20][21][22][23] endocrine modulators, natural products, [24][25][26][27] and others. [28][29][30][31][32][33][34] In these cases, the often covalently grafted organometallic unit is usually inert to ligand substitution, but potentiates the activity of the biomolecule via modification of the pharmacokinetic profile or acts as a structural mimic.…”
Section: Introductionmentioning
confidence: 99%
“…Another class demonstrates the enthusiasm researchers have for grafting metallocenes and metal carbonyls to a variety of biomolecules to modify their biological effects. [12] These therapeutic bioconjugates include steroidal [13][14][15] and nonsteroidal [16][17][18][19][20][21][22][23] endocrine modulators, natural products, [24][25][26][27] and others. [28][29][30][31][32][33][34] In these cases, the often covalently grafted organometallic unit is usually inert to ligand substitution, but potentiates the activity of the biomolecule via modification of the pharmacokinetic profile or acts as a structural mimic.…”
Section: Introductionmentioning
confidence: 99%
“…The N-(3-ferrocenyl-2-naphthoyl) dipeptide ethyl esters 1-4 and the N-(6-ferrocenyl-2-naphthoyl) dipeptide ethyl esters 5-8 shown in Fig. 1 were synthesized as previously reported and spectroscopically characterized by a combination of 1 H NMR, 13 C NMR, DEPT-135 and 1 H-13 C COSY (HMQC) spectroscopy and tandem mass spectrometry. [22] The dipeptide ethyl esters used were GlyGly(OEt) (1,5), AlaGly(OEt) (2,6), GlyPhe(OEt) (3,7) and GlyLeu(OEt) (4,8).…”
Section: Methodsmentioning
confidence: 99%
“…[4] In addition, ferrocene has been incorporated into several different classes of drugs such as antibiotics, anti-malarials and anti-cancer agents. [5][6][7][8][9][10][11][12][13] We have reported the synthesis and structural characterization of N-ferrocenoyl and N-ferrocenyl amino acid and peptide derivatives. [14][15][16][17][18] Preliminary in vitro bioassay results showed that the N-ferrocenyl amino acid and peptide derivatives are cytotoxic against the highly invasive H1299 lung cancer cells.…”
mentioning
confidence: 99%
“…Furthermore, the tetrahydrobenzo[b]thiophene nucleus was adopted as a scaffold for many antimicrobial (Refat and Fadda, 2013), antiviral (Dewal et al, 2012), antiarrhythmic, (Amr et al, 2010), and antitumor (Abbas et al, 2013) activities. A structure activity relationship was established for the heterocyclic compounds derived from benzo[b]thiophene series with antitumor properties were prepared (Ferreirra et al, 2009), as well as a series of N-(2-(5-fluoro-2-(4-fluorophenylthio)benzo [b]thiophen-3-yl)ethyl) acylamides, which were evaluated for their binding affinity and intrinsic activity at melatonin receptors (Mésangeau et al, 2011). Also, benzothiophenes offer interest to pharma industry as scaffolds for synthesis of raloxifene and relevant structural analogs of selective estrogen receptor modulators (SERM) (Dadiboyena, 2012).…”
Section: Introductionmentioning
confidence: 99%